(untitled) (Research, Society and Development, 2024)
Molar Incisive Hypomineralization (HMI) is a defect in the development of enamel of systemic origin, there is a disharmony in enamel-forming cells, during prenatal, natal or postnatal, resulting in demineralization of tooth enamel. The proposed treatments vary and go according to the degree and location of the HMI, and may be aimed at prevention, rehabilitation and even the extraction of the dental element. The objective of this study is to describe the possibilities of treatments available for HMI, assisting the dental surgeon in deciding the treatment indicated for each degree of HMI, through a literature review. An integrative literature review was performed through articles selected through queries to the Google Scholar and National Library of Medicine (PubMed) databases, using 16 articles, published in Portuguese and English, which demonstrated the possibilities of treatments available in cases of HMI. According to studies carried out in this research, eighteen different methods were observed that can be used for treatment in patients with HMI, the most used methods were: desensitizing and remineralizing agents, fluoride varnish, ionomeric sealants, resinous sealants, restorations with composite resin, microabrasion and tooth extraction. The treatments available range from prevention and control of the diet, to tooth extraction, in severe cases where there is no possibility of treatment. It is necessary the periodic follow-up of patients with HMI, so the professional will provide a better quality of life to patients affected by this condition.